How regulation affects network and service quality in related markets - Justus Haucap; Gordon J. Klein (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
We analyze how network regulation affects investment into network infrastructure and complementary services. While regulation negatively affcets investment incentives in the regulated network market, the effects of network regulation on investment in complementary services can be either negative or positive, depending on the relative weight consumers assign to infrastructure versus service quality. We also find constellations, where regulation can enhance perceived total quality.
Keywords: D43; L13; L51; L96; 330